Exploring Innovative Teaching Methods for the Dubbing Major in the Age of Artificial Intelligence - Zhang, Yuyun; Cui, Xiangzhe; Wang, Yiming (Journal of Educational Research and Policies, 2025)
Today, with the rapid development of artificial intelligence, the dubbing industry has ushered in brand-new opportunities and challenges. However, the traditional teaching mode of dubbing major has significant deficiencies in the cultivation of personalized expression and emotional resonance ability, which makes it difficult for students to meet the current employment environment and market needs. This paper aims to propose a series of innovative countermeasures of teaching mode by analyzing the shortcomings of traditional teaching mode. These innovative countermeasures can not only improve the effectiveness of dubbing teaching, but also cultivate excellent dubbing talents with both modern technical literacy and practical ability, so as to provide important support for the sustainable development of dubbing major.